Analisis Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Keputusan Pembelian Smartphone Samsung (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta Tahun 2016) - Ahyar, Risya Muhrisul, Drs. Ma'ruf,MM (2016)
This study aimed to determine the effect of consumer behavior in the samsung smartphone purchase decision. The independent variable of this research is consumer behavior variables represented by cultural, social, personal and psychological. While the dependent variable is the Samsung smartphone purchase decision. This research is quantitative using primary data of respondents. From the classic assumption test results can be seen that the data used in this study are normally distributed, free of symptoms multikoliniearitas, and does not occur heterokedastisitas. That way the data used in this study are qualified to be able to use multiple linear regression model, so that the assumptions contained in the multiple linear regression model can be met Variable cultural, social, personal, not significant effect on the purchase decision variables. The independent variables others are psychologically positive significant effect on purchasing decisions. Rsquare value in this study of 0,559 means that 55.9% variable purchase decision can be explained by the independent variable (cultural, social, personal, psychological).While the rest of 44.1% is explained by other factors that are not included in this study. Variable cultural, social, personal and psychological together (simultaneously) significantly influence the purchase decision variable. Can be seen from the results if the data obtained F value of 18,777dengan signikansi 0,000 <0,05